A universal approach for calculating the Judd–Ofelt parameters of RE3+ in powdered phosphors and its application for the β-NaYF4:Er3+/Yb3+ phosphor derived from auto-combustion-assisted fluoridation. Issue 23 (30th May 2018) - Zhang, Yanqiu; Chen, Baojiu; Xu, Sai; Li, Xiangping; Zhang, Jinsu; Sun, Jiashi; Zhang, Xiangqing; Xia, Haiping; Hua, Ruinian
Abstract : A universal J–O calculation method for phosphors was proposed and used for NaYF4 :Er 3+ /Yb 3+ . Abstract : It is difficult to calculate the Judd–Ofelt (J–O) parameters for trivalent rare earth (RE)-doped powders due to the unavailable absorption spectrum that is necessarily used in the conventional J–O calculation procedure. In this study, a universal method starting from the diffuse-reflection spectrum for calculating the J–O parameters of RE 3+ -doped powdered samples was proposed. In this proposed method, by taking the Kubelka–Munk function into account, the absorption cross-section spectrum was derived from the diffuse-reflection spectrum in the RE 3+ -doped powdered sample using the connection between the absorption cross section and the radiative transition rate of RE 3+ . Then, the J–O parameters might be calculated from the absorption cross-section spectrum via the traditional J–O calculation technique. The NaYF4 :Er 3+ /Yb 3+ and NaYF4 :Er 3+ phosphors were prepared via an auto-combustion-assisted fluoridation technique, and the J–O calculation was carried out for the obtained samples. The obtained J–O parameters were compared with those reported in the literature and also verified by comparing the calculated radiative transition lifetimes with the experimental values. Finally, it was deduced that the proposed J–O calculation route was practicable.